LAMINAR NATURAL CONVECTIVE HEAT TRANSFER IN PARABOLIC ENCLOSURES - Ola Kamiyo (Faculty of Engineering, University of Kufa, 2021)
A finite volume analysis of laminar natural convection of air within full parabolic enclosures heated from below is reported for the enclosure aspect ratio 0.27 £ AR £ 0.7 and a range of the Rayleigh number 5.5 x 106 £ Ra £ 9.8 x 107. The shape of the enclosures strongly affects the results obtained. Quasi-symmetrically arranged counter-rotating vortices are formed in each of the enclosures. The shape of the cells are influenced by the bounding curved and flat surfaces as they change from being rectangular at the periphery to circular at the core. There are reduction in the size and intensity of the on the cells from the center to the bottom corners. At steady state, there exists in each enclosure a central thermal plume that thickens as the roof pitch angle increases. The heat transfer pattern matches the flow of the plumes and jets from the walls. For the 15o roof pitch enclosure, the heat transfer rate increases sharply at a critical Ra value of 5 x 106.